Sociotechnical innovations for low emissions food systems: A state of the art for the Amazon - Clavijo Ponce, Neidy Lorena (2024)
Fighting Amazon deforestation and adopting low-emission agriculture presents a double win: strengthening local food systems' resilience to climate change while contributing to global climate mitigation efforts. However, a one-size-fits-all approach won't work. The key lies in fostering local innovation that considers the specific context and leverages the knowledge of local communities. This "sociotechnical innovation" empowers farmers to design, implement, and maintain solutions that utilize the Amazon's unique biophysical resources. Examples include integrating trees with pastures for livestock or incorporating ecological practices into crop production. While this report separates livestock and agriculture, these activities often function together in the Amazon, and so can the solutions for reducing emissions.